Real-time Interaction Platform for Classroom Teaching Based on Smart Phone APP. Issue 6 (February 2019) - Wang, Feng; Hu, Yujun; Lin, Lanfen
Abstract: Recently the popularity of smart phones has promoted communication for daily life, but it also brings new challenges for current classroom teaching. For example, some students spend too much time on playing phones instead of learning in the classroom. How to effectively instruct students to use phones and promote teaching becomes a very tricky problem. In order to deal with this problem, we propose a new real-time interaction platform for classroom teaching based on smart phone APP, which adopts the extensive multilayer framework and the quantifiable real-time interaction. In this platform, it's easy for teachers to set questions at any time or place, start exercises in class and view real-time statistical analysis results. And it's also easy for students to answer questions in exercises and view results after finishing exercises. What's more, this platform can strengthen the interaction between teachers and students, and stimulate the interest of all students to participate in classroom learning. Results show that our platform can improve teaching effect.